Manual on potato production through zero tillage and straw mulch - Kakraliya, S.; Gatto, M.; Ramírez, D.; Kreuze, Jan F.; Kumar, B. (International Potato Center, 2024)
This guide encapsulates over half a decade of dedicated practice and refinement of Potato Zero Tillage with Rice Straw Mulch (PZTM) across India’s Assam and Bihar regions, and Bangladesh. It distills insights from more than two years of rigorous on-station and on-farm trials. Our collective journey has consistently highlighted PZTM’s superiority to traditional potato farming methods, showcasing a marked reduction in labor and inputs, an uptick in profitability, and improved soil vitality. Moreover, it presents a practical and viable solution for the surplus of crop residues. With this manual, we aim to distill the essence of PZTM into accessible, actionable knowledge for farmers and agricultural extension workers. It is our earnest hope that this manual will not only impart valuable insights into PZTM but also catalyze its widespread adoption, yielding benefits for farmers and fostering environmental stewardship.